The Anticancer Effect of Genistein Through Enhancing PERK Signaling and Suppressing the IRE1α-XBP1 Axis in Canine Mammary Gland Tumor Cells - Ye-Ji Jang; Min-Jae Yoo; Hyuk Jang; Jun Song; Sang-Youel Park; Jawun Choi; Jae-Won Seol (Animals, 2025)
Genistein, a natural isoflavone, exerts anticancer effects on human breast cancer cells by modulating the unfolded protein response (UPR). However, the effect of genistein on UPR in canine mammary gland tumor (CMT) cells remains unknown. The aim of the present study was to investigate the anticancer effects of genistein on CMT-U27 cells, focusing on the regulation of UPR-related pathways and the associated cell death mechanisms. CMT-U27 cells were treated with genistein. Cell viability, apoptosis, and UPR-related protein expression were analyzed using MTS assay, Annexin V-Propidium Iodide (PI) staining, Western blotting, and immunocytochemistry. Genistein treatment significantly reduced cell viability and induced apoptosis, accompanied by an increased Bcl-2-associated X (Bax) ratio of B-cell lymphoma-2 (Bcl-2) and cleaved caspase-8 and caspase-3. On regulation of the UPR system, genistein treatment showed a dual-function by enhancing the protein kinase R-like endoplasmic reticulum kinase (PERK) signaling while suppressing the inositol-requiring enzyme 1 alpha (IRE1α)–X-box-binding protein 1 (XBP1) axis. Furthermore, genistein downregulated estrogen receptor alpha (ERα), which may contribute to the inhibition of IRE1α signaling through a disrupted positive feedback loop. These findings suggested that genistein modulates the UPR to induce apoptosis in CMT-U27 cells, highlighting its potential as a therapeutic or adjuvant agent for CMTs.